2022
DOI: 10.1007/s40200-022-01157-2
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship of photobiomodulation therapy and oxidative stress markers in healing dynamics of diabetic neuropathic ulcers in Wistar rats

Abstract: Purpose: Diabetic foot ulcers are reported to be the most expensive complications of diabetes, with high morbidity and mortality rates. If the necessary care is not provided for the wound to heal, the individual may end up amputating the affected feet. Photobiomodulation therapy is a promising non-pharmacological treatment option for wound healing. The objective of the present study is to establish a dose-response relationship between photobiomodulation therapy and oxidative stress markers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In addition, Karkada et al discovered an effective rise in the antioxidant enzyme (i.e., malondialdehyde, superoxide dismutase and glutathione) of the rats treated with PBMT of dosages 4, 6, and 8 J/cm 2 , which accelerates the scavenging of the ROS molecules during the wound healing process. 27 Although the systemic mechanism of action of PBMT on human brain function has not been completely elucidated, several studies have observed that PBMT exerts beneficial effects on brain nerve cells and tissues. Giuliani et al found that red and NIR light have neuroprotective effects, promoting neurogenesis and inhibiting neuronal apoptosis.…”
Section: Mechanism Of Action Of Pbmtmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Karkada et al discovered an effective rise in the antioxidant enzyme (i.e., malondialdehyde, superoxide dismutase and glutathione) of the rats treated with PBMT of dosages 4, 6, and 8 J/cm 2 , which accelerates the scavenging of the ROS molecules during the wound healing process. 27 Although the systemic mechanism of action of PBMT on human brain function has not been completely elucidated, several studies have observed that PBMT exerts beneficial effects on brain nerve cells and tissues. Giuliani et al found that red and NIR light have neuroprotective effects, promoting neurogenesis and inhibiting neuronal apoptosis.…”
Section: Mechanism Of Action Of Pbmtmentioning
confidence: 99%
“…In addition, Karkada et al. discovered an effective rise in the antioxidant enzyme (i.e., malondialdehyde, superoxide dismutase and glutathione) of the rats treated with PBMT of dosages 4, 6, and 8 J/cm 2 , which accelerates the scavenging of the ROS molecules during the wound healing process 27 …”
Section: Mechanism Of Action Of Pbmtmentioning
confidence: 99%